A primary science curriculum development in a small Caribbean island - King, Winston K. (International Council of Associations for Science, 1980)
This case study describes the rationale and strategy used in the development of a primary science curriculum, and identifies the roles played by science teachers, personnel in the Ministry of Education, and educational consultants in its development, diffusion, and implementation
Keywords: Primary school science